Synthesis of Amino-ADT Provides Access to Hydrolytically Stable Amide-Coupled Hydrogen Sulfide Releasing Drug Targets - Hammers, Matthew D.; Singh, Loveprit; Montoya, Leticia A.; Moghaddam, Alan D.; Pluth, Michael D. (Synlett, 2016)
As additional physiological functions of hydrogen sulfide (H2S) are discovered, developing practical methods for exogenous H2S delivery is important. In particular, nonsteroidal anti-inflammatory drugs (NSAIDs) functionalized with H2S-releasing anethole dithiolethione (ADT-OH) through ester bonds are being investigated for their combined anti-inflammatory and antioxidant potential. The chemical robustness of the connection between drug and H2S-delivery components, however, is a key and controllable linkage in these compounds. Because esters are susceptible to hydrolysis, particularly under acidic conditions such as stomach acid in oral drug delivery applications, we report here a simple synthesis of amino-ADT (ADT-NH2) and provide conditions for successful ADT-NH2 derivatization with the drugs naproxen and valproic acid. Using UV-vis spectroscopy and HPLC analysis, we demonstrate that amide-functionalized ADT derivatives are significantly more resistant to hydrolysis than ester-functionalized ADT derivatives.
Keywords: sulfur; dithiolethione; ADT-OH; hydrogen sulfide; H2S donors